2021
DOI: 10.1002/biot.202100413
|View full text |Cite
|
Sign up to set email alerts
|

Single‐strand annealing: Molecular mechanisms and potential applications in CRISPR‐Cas‐based precision genome editing

Abstract: Background: Spontaneous double-stranded DNA breaks (DSBs) frequently occur within the genome of all living organisms and must be well repaired for survival.Recently, more important roles of the DSB repair pathways that were previously thought to be minor pathways, such as single-strand annealing (SSA), have been shown.Nevertheless, the biochemical mechanisms and applications of the SSA pathway in genome editing have not been updated. Purpose and Scope:Understanding the molecular mechanism of SSA is important t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 149 publications
1
18
0
Order By: Relevance
“…For example, it has been reported that deficiency of ERCC1, a component of the excision nuclease complex (ERCC1-XPF), activated during SSA, results in synthetic lethality after olaparib treatment [ 83 ]. Moreover, reports suggest that PARP-1 modulates the activity of FEN-1; a protein also involved in RAD52-mediated SSA [ 84 , 85 ]. However, as PARP-1, ERCC1-XPF and RAD52 are shown to be involved in multiple DNA repair pathways, this makes it difficult to establish specific roles of PARP-1 in SSA.…”
Section: Parp-1 Operates At the Heart Of Dna Damage Response And Dna ...mentioning
confidence: 99%
“…For example, it has been reported that deficiency of ERCC1, a component of the excision nuclease complex (ERCC1-XPF), activated during SSA, results in synthetic lethality after olaparib treatment [ 83 ]. Moreover, reports suggest that PARP-1 modulates the activity of FEN-1; a protein also involved in RAD52-mediated SSA [ 84 , 85 ]. However, as PARP-1, ERCC1-XPF and RAD52 are shown to be involved in multiple DNA repair pathways, this makes it difficult to establish specific roles of PARP-1 in SSA.…”
Section: Parp-1 Operates At the Heart Of Dna Damage Response And Dna ...mentioning
confidence: 99%
“…Prior studies have identified proteins involved in SSA in fungi, invertebrates, and mammalian cell lines (reviewed in Bhargava et al 2016 ; Vu et al 2022 ). Studies in budding yeast found that loss of Rad52 or its paralog Rad59 resulted in near complete ablation of SSA ( Sugawara and Haber 1992 ; Ivanov et al 1996 ; Sugawara et al 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have identified proteins involved in SSA in fungi, invertebrates, and mammalian cell lines (reviewed in BHARGAVA et al 2016;VU et al 2022). Studies in budding yeast found that loss of Rad52 or its paralog Rad59 resulted in near complete ablation of SSA (SUGAWARA AND HABER 1992;IVANOV et al 1996;SUGAWARA et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have identified proteins involved in SSA in fungi, invertebrates, and mammalian cell lines (reviewed in B hargava et al . 2016; V u et al . 2022).…”
Section: Introductionmentioning
confidence: 99%